Participatory Budgeting and Financial Sustainability in the Local Governments in Uganda: A Case Study of Kabale District Local Government - Tugumisirize, Winfred (Kabale University, 2025)
This study examined the effect of participatory budgeting on financial sustainability in Kabale District Local Government, Uganda. The research objectives were to examine the influence of budget formulation on financial sustainability, analyze the effect of budget approval on financial sustainability, assess the influence of budget implementation on financial sustainability, and ascertain the effect of participatory budgeting onfinancial stability when mediated by government policies. The study adopted a cross-sectional research design using Kabale Districtas a case study. A population of 3600 was targeted from which a samplesize of 360 respondents was selected using purposivesampling and conveniencesampling. Data were analyzed using descriptive statistics, correlation, and regression analysis. The study found a significant positive relationship betweenparticipatory budgeting practicesand financial sustainability. The studyfurther found that budget formulation plays a critical role in enhancing financial sustainability. Budget formulation and implementation had the strongest influence on financial sustainability. Genderhad no significant moderating effect onthe relationship between participatory budgeting and financial sustainability. The study concluded that participatory budgeting enhances financial sustainability in local governments. The study recommends strengthening citizen engagement in all budget phases, enhancing transparency in budget processes, and gender exclusivity to support participatory budgeting initiatives for improved financial sustainability in local governments.